Factors Associated with Attempt for Smoking Cessation among Hardcore Smokers in Taiwan - Hui-Wen Huang; Ya-Hui Yang; Wen-Wen Li; Chih-Ling Huang (JMIR Publications, 2021)
Background: Tobacco control activities have mostly influenced those smokers who found it easier to quit and, thus, remaining smokers are those who are less likely to stop smoking. This phenomenon is called "hardening hypothesis," which individuals unwilling or unable to quit smoking and likely to remain so. The aim of this study was to identify the factors correlated with smoking cessation among hardcore smokers. Methods: A cross-sectional descriptive correlational research design was employed. Hardcore smokers from communities in Taiwan were recruited to participate in the study (N = 187). Self-report questionnaires were used to collect demographic data as well as data on nicotine dependence, quitting self-efficacy, social smoking motives, attitudes towards the Tobacco Hazards Prevention Act (THPA), and smoking cessation. Logistic regression analysis was used to examine the factors that were related to quit smoking. Results: About 30.3% (n = 54) reported having experienced quitting smoking over 7 days in the past year. Logistic regression analysis indicated that attitudes towards the THPA was identified as a particularly important factor contributing to the increase in smoking cessation among hardcore smokers. Conclusions: Nurses should cooperate with smoking cessation coaches to facilitate the improvement of attitudes towards the THPA as a key means through which to increase the smoking cessation rate among hardcore smokers.